2016
DOI: 10.1002/adma.201504894
|View full text |Cite
|
Sign up to set email alerts
|

Design of Novel Visible Light Active Photocatalyst Materials: Surface Modified TiO2

Abstract: Type of publicationArticle (peer-reviewed) AbstractThis progress review describes our work on the design of new TiO2 based photocatalysts. The key concept is the formation of composite structures through the modification of anatase and rutile TiO2 with molecular-sized nanoclusters of metals oxides. Our density functional theory (DFT) level simulations have been compared with experimental work synthesizing and characterizing surface modified TiO2. We use DFT to show that nanoclusters of metal oxides such as Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(120 citation statements)
references
References 107 publications
4
110
0
Order By: Relevance
“…The smaller semicircle in the EIS Nyquist plot suggests a fast interfacial charge transfer in the semiconductor. 58,59 This result also demonstrates that the 1D Ag@CdS hierarchical nanowires display superior efficiency compared to that of the CdS nanoflower in separating the electron-hole pairs, which is consistent with the results of PL spectroscopy.…”
Section: Inorganic Chemistry Frontiers Research Articlesupporting
confidence: 87%
“…The smaller semicircle in the EIS Nyquist plot suggests a fast interfacial charge transfer in the semiconductor. 58,59 This result also demonstrates that the 1D Ag@CdS hierarchical nanowires display superior efficiency compared to that of the CdS nanoflower in separating the electron-hole pairs, which is consistent with the results of PL spectroscopy.…”
Section: Inorganic Chemistry Frontiers Research Articlesupporting
confidence: 87%
“…As a matter of fact, in the EIS Nyquist plot, the smaller semicircle size indicates fast interfacial charge transfer in the semiconductor. 47,48 The above result suggests that more effective interfacial charge transfer occurs on the twinned anatase TiO 2 photocatalyst rather than anatase and brookite TiO 2 under these conditions. Based on these results, it was concluded that the enhancement of the photocatalytic hydrogen evolution activity of the twinned anatase TiO 2 nanocrystals was attributed to the faster separation of photogenerated carriers and lower recombination of photoinduced electron-hole pairs.…”
Section: Resultsmentioning
confidence: 82%
“…Despite that, pure unmodified TiO 2 suffers from several drawbacks such as low quantum efficiency resulting from rapid recombination of charge carriers and the limit to UV-light absorption due to its wide band gap [29][30][31][32][33]. Great endeavours have been made to resolve these drawbacks, including cationic metal and anionic doping to manipulate the properties of TiO 2 [34][35][36][37][38][39][40][41][42][43][44]. However, these techniques could result in the generation of secondary impurities and oxygen vacancies, respectively, which could ultimately reduce the photocatalytic activity of TiO 2 [45,46].…”
Section: Introductionmentioning
confidence: 99%